Doença reumática auto referida e presença de dor em idosos no interior do Amazonas - Silva, Geuziane Souza da (Brasil, 2021)
The presence of referred rheumatic disease and pain in elderly people from the interior of Amazonas were identified and described. A total of 131 elderly people living in the interior of Amazonas were visited. The Functional Comorbidity Index (FCI) was used to track the presence of self-reported diseases, and the Numerical Scale and Sensitive Faces Scale for Low Education and Cognitive Changes were used to assess pain. . Most of the elderly in this study did not present rheumatic diseases, however, most of them report moderate to severe pain, especially in the lumbar spine, knees and legs, and do not have a functional clinical diagnosis even with signs of rheumatic diseases.